Levantamiento geomorfológico a escala 1:25000 de la parroquia rural Jimbilla, perteneciente al cantón Loja, provincia de Loja” - Jessica Alexandra Armijos Armijos, Jessica Alexandra (2021)
The present degree work is oriented in the elaboration of a geomorphological survey to scale 1:25000 of the rural parish Jimbilla, which allows the analysis and understanding of geomorphology in the territory, in addition to the importance of the implementation of programs such as ArcGis 10.5 and ENVI 5.3 for the characterization and modeling of relief in a specific place. As a basis for the determination of the geomorphology, we worked with the Methodology implemented by the Ministry of the Environment with respect to the Model of Geomorphological Units for the Cartographic Representation of Ecosystems of Continental Ecuador, for which it was necessary the use of a Digital Elevation Model obtained from ALOS PALSAR with a resolution of 12.5 x 12.5 meters and Orthophotos of scale of 1:5,000 of SIGTIERRAS, , the same ones that form a key factor for the development and completion of the project. Topographic indexes were obtained, an automatic classification or unsupervised classification (ISODATA), neighborhood analysis and elimination of redundant information such as noise, leading to the generation of morphometry, which was analyzed and delimited in ArcGis and classified in a hierarchical order, thus obtaining a general mountain relief, two geomorphological units of macro relief such as mountain range and foothills and five geoforms of meso-relief which are mountain relief, mountain range slope, gorge, foothill slope and terraces, which were validated with 66 points for a more accurate information of the geomorphology of the study area. Keywords: geomorphology, territory, relief, cartography, automatic classification.